2020
DOI: 10.3390/cells9030740
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Promotes Parkinson’s Disease through Aberrant Expression of α-Synuclein, Mitochondrial Dysfunction, and Deregulation of the Polo-Like Kinase 2 Signaling

Abstract: Background: Insulin resistance (IR), considered a hallmark of diabetes at the cellular level, is implicated in pre-diabetes, results in type 2 diabetes, and negatively affects mitochondrial function. Diabetes is increasingly associated with enhanced risk of developing Parkinson’s disease (PD); however, the underlying mechanism remains unclear. This study investigated the probable culpability of IR in the pathogenesis of PD. Methods: Using MitoPark mice in vivo models, diabetes was induced by a high-fat diet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 55 publications
1
52
0
1
Order By: Relevance
“…Insulin resistance is the hallmark of diabetes at the cellular level and negatively affects mitochondrial function [88]. Our IPA analysis suggests that several relevant canonical pathways are affected by T2DM, i.e., Mitochondrial Dysfunctions and Insulin Receptor Signaling (Figure 2).…”
Section: Altered Pathways In T2dmmentioning
confidence: 84%
“…Insulin resistance is the hallmark of diabetes at the cellular level and negatively affects mitochondrial function [88]. Our IPA analysis suggests that several relevant canonical pathways are affected by T2DM, i.e., Mitochondrial Dysfunctions and Insulin Receptor Signaling (Figure 2).…”
Section: Altered Pathways In T2dmmentioning
confidence: 84%
“…IR also led to increased prolonged oxidative stress and raised aberrant section of α-synuclein. They noticed increased expression of α-synuclein in the diabetic MitoPark mice and enhanced degeneration of the dopaminergic neurons [19]. Moreover, IR leads to increased α-synuclein, oxidative stress, and mitochondrial dysfunction in differentiated human dopaminergic cells [5,19].…”
Section: Insulin Resistance (Ir) As a Cross-link Between Dm And Pdmentioning
confidence: 99%
“…They noticed increased expression of α-synuclein in the diabetic MitoPark mice and enhanced degeneration of the dopaminergic neurons [19]. Moreover, IR leads to increased α-synuclein, oxidative stress, and mitochondrial dysfunction in differentiated human dopaminergic cells [5,19]. A study carried out in insulin-resistant mice revealed a loss of dopaminergic neurons and abnormal movement similar to PD.…”
Section: Insulin Resistance (Ir) As a Cross-link Between Dm And Pdmentioning
confidence: 99%
“…In addition, diabetes and poor blood sugar control are linked to fast deterioration and worse PD severity ( Cereda et al, 2012 ; Kotagal et al, 2013 ). Although insulin resistance or diabetes enhances PD-related pathogeneses in in vivo and in vitro neuronal models ( Bousquet et al, 2012 ; Solmaz et al, 2017 ; Hong et al, 2020 ), biological evidence in human studies is lacking and the functional assessment of insulin signaling pathway in PD patients’ neurons is challenging. The fasting or postprandial blood glucose and HbA1c test reflect the pancreatic islet function but not insulin resistance ( Desimone and Weinstock, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer disease (AD), the most common neurodegenerative disease, is speculated to be associated with neural insulin resistance because the major AD pathogeneses, such as neurofibrillary tangles, neuroinflammation, oxidative stress, and neurodegeneration, are all associated with neural insulin resistance ( Arnold et al, 2018 ). Furthermore, several studies have suggested that diabetes increases the risk of or accelerates the progression of Parkinson’s disease (PD), ( Hu et al, 2007 ; Cereda et al, 2011 ; Sun et al, 2012 ; Lu et al, 2014 ; Hong et al, 2020 ). Moreover, no biomarker evidence exists to confirm the association between PD and neural insulin resistance.…”
Section: Introductionmentioning
confidence: 99%